2017
DOI: 10.1310/sci2302-131
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of a Mobile Touchscreen Interface for Assistive Robotic Manipulators: A Pilot Study

Abstract: Background: Assistive robotic manipulators (ARMs) have been developed to provide enhanced assistance and independence in performance of daily activities among people with spinal cord injury when a caregiver is not on site. However, the current commercial ARM user interfaces (UIs) may be difficult to learn and control. A touchscreen mobile UI was developed to overcome these challenges. Objective: The object of this study was to evaluate the performance between 2 ARM UIs, touchscreen and the original joystick, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In this context, Chung et al [ 30 ] investigated the performance of a tablet-based UI versus a conventional joystick control in a comparative pilot study with 8 participants with upper extremity impairments using a JACO (Kinova) robotic manipulator. The use of the touch screen UI resulted in high execution speeds and low task completion times compared with the conventional control form; however, no equal distribution of UI users was realized within the study.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, Chung et al [ 30 ] investigated the performance of a tablet-based UI versus a conventional joystick control in a comparative pilot study with 8 participants with upper extremity impairments using a JACO (Kinova) robotic manipulator. The use of the touch screen UI resulted in high execution speeds and low task completion times compared with the conventional control form; however, no equal distribution of UI users was realized within the study.…”
Section: Discussionmentioning
confidence: 99%
“…While many 3D input devices have been developed, lowdimensional input devices such as joysticks and computer mice are still widely used in professional teleoperation systems such as surgical robots [20], assistive robots [21], disaster rescue robots [22], and space exploration robots [23]. Different kinds of 2D input devices have been used for a human operator to specify the position of a robot endeffector, including joysticks [24]- [27], computer mice [28], and touch screens [29], [30]. Prior research has found lowdimensional input devices to be more accurate, comfortable, and easier to use for inexperienced operators over 3D input devices [23], [27], [31], [32].…”
Section: Telemanipulation With Low-dimensional Input Devicesmentioning
confidence: 99%
“…Research in this area has focused on developing new ways to control ARMs, including new control interfaces [5,6], remapping control inputs [7], and shared-control schemes [3,8]. Most of the work on new control interfaces has aimed to provide an alternative means of ARM control such as voice control [9], gaze control [10,11], tongue control [12], braincomputer interface control [13], body movement control via inertia measurement units (IMUs) [14], and gesture control via computer vision [15].…”
Section: Introductionmentioning
confidence: 99%